80 Does the Risk of Obstructive Sleep Apnea (OSA) Affect Erectile Function Recovery (EFR) After Radical Prostatectomy (RP)?. Issue 1 (1st April 2022) - Martinez, JM Flores; Salter, CA; Ruiz, K; Benfante, N; Schofield, E; Tan, M; Laudone, V; Mulhall, JP
ABSTRACT: Introduction: Obstructive sleep apnea (OSA) affects as many as 7% of adult men in the general population, higher in men with obesity and large neck sizes. OSA is associated with ED. No data to date has assessed EFR after RP in men with OSA. Objective: The objective of this study was to define EFR rates 2 years post-RP. Methods: Records of men who underwent RP with 24-month post-RP follow-up were reviewed. ADT and radiation therapy were exclusions. Men completed the OSA screening questionnaire, STOP-BANG (SB) pre-RP. Men were divided into OSA risk groups: high, intermediate, and low. EFR was recorded using IIEF-EFD score, with a score of at least 24 indicating recovery. Univariable and multivariable logistic regression analyses assessed predictors of EFR. Results: 454 men were analyzed. Mean age 62 ± 7 years. Of the studied population, 12% had a history of OSA, 10% had diabetes, 12% were current smokers, and 37% were former smokers. The median STOP-BANG (SB) score was 2. High, intermediate, and low risk of OSA scores were 8%, 41% and 51% respectively. Mean baseline testosterone (T) was 495 ng/dL, PSA 7.4 ng/mL, and EFD score 22. Most men had a Gleason sum of 7 (87%). 73% of patients had bilateral or unilateral neurovascular bundle preservation. At the 2-year follow up, median EFD score in high, intermediate and low OSA risk groups: were 9, 16, and 18 respectively. The low OSA risk group was significantly more likely to recover (OR = 1.6, 1.1 – 2.4) than the moderate/high group. Younger age (OR = 0.92, 0.89 – 0.95), absence of diabetes (OR = 0.31, 0.14 – 0.72), higher baseline T (OR per 100 units = 1.40, 1.04 – 1.89), higher baseline EFD score (OR = 1.16, 1.11 – 1.22), and lower Gleason score (OR = 0.53, 0.34 – 0.82) were also associated with recovery at 2 years. Conclusions: In our cohort, at 2 years post-RP, increasing OSA risk is associated with poorer EFR in men post-RP. Disclosure: No